Ergodicity and model quality in template‐restrained canonical and temperature/Hamiltonian replica exchange coarse‐grained molecular dynamics simulations of proteins. Issue 31 (22nd September 2017) - Karczyńska, Agnieszka S.; Czaplewski, Cezary; Krupa, Paweł; Mozolewska, Magdalena A.; Joo, Keehyoung; Lee, Jooyoung; Liwo, Adam
Abstract : Molecular simulations restrained to single or multiple templates are commonly used in protein‐structure modeling. However, the restraints introduce additional barriers, thus impairing the ergodicity of simulations, which can affect the quality of the resulting models. In this work, the effect of restraint types and simulation schemes on ergodicity and model quality was investigated by performing template‐restrained canonical molecular dynamics (MD), multiplexed replica‐exchange molecular dynamics, and Hamiltonian replica exchange molecular dynamics (HREMD) simulations with the coarse‐grained UNRES force field on nine selected proteins, with pseudo‐harmonic log‐Gaussian (unbounded) or Lorentzian (bounded) restraint functions. The best ergodicity was exhibited by HREMD. It has been found that non‐ergodicity does not affect model quality if good templates are used to generate restraints. However, when poor‐quality restraints not covering the entire protein are used, the improved ergodicity of HREMD can lead to significantly improved protein models. © 2017 Wiley Periodicals, Inc. Abstract : Illustration of the difference between restrained temperature multiplexed replica exchange molecular dynamics (MREMD, top) and restrained Hamiltonian multiplexed replica exchange molecular dynamics (HREMD, bottom). Exchange of temperatures only (MREMD) can result in getting trapped in topological mirror image structures (top right), while adding exchanges of the restraint weights (HREMD) enables the system to escape from such structures, owing to the weakening or removing restraints in a part of a trajectory (bottom right).